CHANGED RULES OF LIMITED PARTNERSHIPS IN THE HUNGARIAN CIVIL CODE- WITH PARTICULAR REFERENCE TO THE MANAGEMENT AMENDMENTS - Lénárdné Maletics, Borbála Lénárdné Maletics (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Abstract The Act XCV of 2021 amending Act V of 2013 on the Civil Code (hereinafter: Civil Code) introduced significant changes concerning business associations in Hungary. In my study, I will examine certain amendments affecting limited partnerships, with a particular reference on the rules for the election of a limited partner as managing director and whether the corporate form is shifting from limited partnership to capital partnership under the changed provisions.